PiRBase: a comprehensive database of piRNA sequences. Issue Volume 47:Issue D1(2019) (29th October 2018) - Wang, Jiajia; Zhang, Peng; Lu, Yiping; Li, Yanyan; Zheng, Yu; Kan, Yunchao; Chen, Runsheng; He, Shunmin
Abstract: PIWI-interacting RNAs are a class of small RNAs that is most abundantly expressed in animal germline. Substantial research is going on to reveal the functions of piRNAs in the epigenetic and post-transcriptional regulation of transposons and genes. To collect and annotate these data, we developed piRBase, a database assisting piRNA functional study. Since its launch in 2014, piRBase has integrated 264 data sets from 21 organisms, and the number of collected piRNAs has reached 173 million. The latest piRBase release (v2.0, 2018) was more focused on the comprehensive annotation of piRNA sequences, as well as the increasing number of piRNAs. In addition, piRBase release v2.0 also contained the potential information of piRNA targets and disease related piRNA. All datasets in piRBase is free to access, and available for browse, search and bulk downloads at http://www.regulatoryrna.org/database/piRNA/ .